Elmo$1 (Bs ducky day s - Albee, Sarah; Chartier, Normand, 1945- (New York : Random House, 2000)
Everyone must make way for Elmo and his five ducklings as he leads them all over town in a search for their missing mother.
"Featuring Jim Henson$1 (Bs Sesame Street Muppets."s
Keywords: Ducks -- Fiction; City and town life -- Fiction; Mother and child -- Fiction; Puppets -- Fiction